PELATIHAN MENDELEY DESKTOP BAGI IKATAN MAHASISWA KEPERAWATAN DI KOTA TOBELO UNTUK MENINGKATKAN KEMAMPUAN MENULIS ARTIKEL ILMIAH - Akerina, Febrina Olivia; Kour, Femsy (HIRONO : Jurnal Pengabdian Masyarakat, 2021)
The results of the researcher's thoughts, in this case students, must be published by following the rules of writing well and correctly. Using the citation application makes it easier to write a bibliography compared to the manual method. This workshop aims to introduce the Mendeley desktop application, how to install it, and its use in making scientific articles, as well as to increase students' knowledge about Mendeley desktop. Based on the evaluation, it appears that the ability of participants has increased. Overall, the difficulties experienced by participants is during the initial install on laptops and integrate Mendeley Microsoft Word with a percentage of 8%. Based on the questionnaire given, 100% of students will use Mendeley in compiling their thesis and scientific articles.